Working as a “Token”: Different Perspectives on the Role of International Faculty in Korean Universities - Inyoung Song; Yangson Kim (ECNU Review of Education)
Purpose This study examined the factors influencing the tokenization of international faculty in Korean universities. It also explored how domestic faculty and staff perceive the role of international faculty and the process by which they adapt to the Korean education system. Design/Approach/Methods The study used a qualitative design. Universities were arranged by region and objectives (research-oriented, teaching-oriented, or combined teaching and research) for sampling, and in-depth interviews were conducted with three groups: international faculty, Korean faculty, and Korean staff. Findings First, Korean faculty and staff expressed low expectations of international faculty based on their different definitions of internationalization. Second, these low expectations resulted in role encapsulation, limiting the functions of international faculty. In addition, although Korean universities compete to hire international faculty, they do not provide them with adequate support post-hire. The burden of this lack of support is often passed on to Korean faculty, instilling a negative perception of international faculty. Originality/Value Using the framework of tokenism, this study analyzed Korean universities’ efforts to hire international faculty as part of university internationalization; it determined whether the latter ultimately became major actors in the internationalization strategy.